Unemployment Insurance and Job Duration in Canada - Christofides, L. N.; McKenna, C. J. (Journal of Labor Economics, 1996)
We use data from the Canadian 2-year longitudinal Labour Market Activity Survey of 1986-87 to estimate the effect of the Unemployment Insurance (UI) system on job duration. Particular attention is focused on the "entrance requirements" of the UI system, which relate eligibility for UI benefits to an individual's recent employment history. The article makes operational the UI entrance requirement provisions which take into account variations in the regional unemployment rate. Controlling for many personal and job characteristics, we find evidence that a significant number of jobs terminate when they have reached the duration that would permit a UI claim.